Foreign Investment in the Economy of Uzbekistan (Global Scientific Review, 2022)
In this article, it is studied that the rational regulation of foreign economic activity is an important component of the state strategy in the economic development of our country and one of its main directions is attracting foreign investments to the republic. The work on attracting foreign investments, the investments made by international financial institutions, the efforts made to gain a place in the world trade of the country were analyzed.